Teachers’ Organizational Commitment: Effects of Support, Servant Leadership, Personality, and Job Satisfaction - Indrati, Briliantina; Susanti, Eni; Hermawan, Andi; Mubarok, Husni; Fauzi, Shukor Sanim Mohd (Universitas Muhammadiyah Surakarta, 2026)
Teachers are a vital part of educational management, and their organizational commitment is crucial for achieving the institution's goals. Organizational commitment reflects teachers' attitudes and feelings toward maintaining membership and carrying out their duties responsibly. Path analysis and SITOREM analysis are the quantitative methods used in this study. This study involved 237 permanent foundation teachers (GTY) from private vocational high schools in Bogor Regency, with a sample of 149 teachers selected using the Slovin formula. The study aimed to find the best methods, techniques, and solutions to increase teacher commitment to the organization by enhancing organizational support, servant leadership, personality, and job satisfaction. The results showed that organizational support, servant leadership, and personality significantly influenced job satisfaction and service quality. Job satisfaction served as a mediator, enhancing the influence of these three factors on service quality. One of the best ways to increase organizational commitment is to improve weak metrics (salary/wages, resource provision, empathy, supportive supervision, extroversion) and maintain strong metrics (coworker relations, emotional stability, conscientiousness, openness, listening, and trust). The results of the study show that job satisfaction is the main key to improving the quality of service and teacher commitment in the organization. These findings have implications for educational management by emphasizing the importance of developing policies based on job satisfaction, servant leadership, and organizational support as innovative strategies to improve service quality and teacher commitment.